2004
DOI: 10.1063/1.1712026
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and magnetic properties of SmCo5.85Si0.90 compound

Abstract: The crystal structure and magnetic properties of SmCo7−xSix (x=0.1–0.9) compounds were studied by means of x-ray powder diffraction and magnetic measurements. Rietveld refinement of x-ray powder diffraction pattern shows that the as-cast compound SmCo7−xSix with x=0.9 crystallizes in the TbCu7-type structure with the space group P6/mmm, and the doping element Si has a distinct preference to occupy the 3g site. According to the refinement result, the composition of the compound is derived as SmCo5.85Si0.90. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 10 publications
0
37
1
Order By: Relevance
“…Many researchers have focused on the SmCo family of permanent magnets, because their Curie temperatures (T C ∼1000 K) are much higher than that of Nd 2 Fe 14 B (T C =588 K), making the former attractive in motor or generator applications where high temperatures could degrade the performance of Nd 2 Fe 14 B systems. Researchers have embarked on many routes to improve the performance of Sm-Co magnetic materials including substitution 6,7 , thin film synthesis 8 , composites, 9 and microstructure modifications [10][11][12] . Like Nd 2 Fe 14 B, Sm 2 Co 17 forms in an anisotropic crystal structure composed of TM and TM-RE atomic planes stacked along a c-axis.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Many researchers have focused on the SmCo family of permanent magnets, because their Curie temperatures (T C ∼1000 K) are much higher than that of Nd 2 Fe 14 B (T C =588 K), making the former attractive in motor or generator applications where high temperatures could degrade the performance of Nd 2 Fe 14 B systems. Researchers have embarked on many routes to improve the performance of Sm-Co magnetic materials including substitution 6,7 , thin film synthesis 8 , composites, 9 and microstructure modifications [10][11][12] . Like Nd 2 Fe 14 B, Sm 2 Co 17 forms in an anisotropic crystal structure composed of TM and TM-RE atomic planes stacked along a c-axis.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…It is reported that SmCo 7 -type alloys have lower coercivity by a general mechanically alloyed method [14]. Recently, the best performance of magnetic properties occurs in textured materials where the easy magnetization axes are all aligned, which increase their remanence and magnetic energy product [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, there has been great scientific interest in SmCo 7 -type alloys due to their potential applications as novel high temperature, rare earth permanent magnets [11][12][13][14]. However, pure SmCo 7 phase is metastable, and it cannot be obtained by general equilibrium methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this context melt-spinning technique provides an alternate approach to develop high coercive single phase magnets. [4][5][6][7] It was also reported that the Cu stabilises 1:7 phase. 8,9 For high coercivity in SmCo 5 magnets, the following structure-property correlations have been understood through detailed studies: i) the presence of high anisotropic SmCo 5 single phase as the matrix, 10 ii) availability of a thin layer of nonmagnetic grain boundary phase to reduce inter-grain magnetic exchange coupling between the neighbouring grains, 11,12 iii) fine grain structure with average grain size in the range of a single domain size (750 nm) to suppress the nucleation of domain walls within the grains, 13,14 and iv) evenly distributed domain wall pinning centres (defects, precipitates and low or high anisotropic secondary phases) within the matrix where the pinning center size is in the range of domain wall thickness of SmCo 5 phase (∼3-4 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Hard magnets based on SmCo 5 (1:5) have been extensively studied on account of the largest magneto-crystalline anisotropy exhibited by the 1:5 phase among the known rare earth transition metal (RE-TM) intermetallic compounds. The experimentally realized coercivity of the 1:5 phase is only 10-20% of H A , 2 and is due to the presence of unavoidable secondary 2:7 and 2:17 phases at the micro level.…”
Section: Introductionmentioning
confidence: 99%